2012
DOI: 10.1155/2013/521045
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Chlorpyrifos‐Contaminated Soils by Laboratory‐Synthesized Zero‐Valent Nano Iron Particles: Effect of pH and Aluminium Salts

Abstract: Degradation of the insecticide chlorpyrifos in contaminated soils was investigated using laboratory synthesized zero-valent nano iron (ZVNI) particles. The synthesized ZVNI particles were characterized as nanoscale sized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The zero-valent state (Fe0) of iron was confirmed by EDAX analysis and the morphology of the ZVNI particles was studied by XRD. Batch experiments were conducted by treating the chlorpyrifos contaminated soil with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Devlin and Allin [11] observed that the reactivity of granular iron during the reduction of 4-chloronitrobenzene was increased by a sulfate, either owing to an increase in the ZVI surface activity or in its sorption capacity. Similar trend of experimental finding was reported by Reddy et al [27], who stated that the degradation rate of chlorpyrifos was greatly enhanced by augmenting Al 2 (SO 4 ) 3 with ZVI. During the ferric nitrate-amended Fe 0 treatment of chlorpyrifos, 44.6, 46.2, and 47.6% of the chlorpyrifos was removed within 24 h after treatment with 0.1, 0.5, and 1.0% (w/v) ferric nitrate, respectively (Fig.…”
Section: Degradation Of Chlorpyrifos By Iron Saltssupporting
confidence: 90%
“…Devlin and Allin [11] observed that the reactivity of granular iron during the reduction of 4-chloronitrobenzene was increased by a sulfate, either owing to an increase in the ZVI surface activity or in its sorption capacity. Similar trend of experimental finding was reported by Reddy et al [27], who stated that the degradation rate of chlorpyrifos was greatly enhanced by augmenting Al 2 (SO 4 ) 3 with ZVI. During the ferric nitrate-amended Fe 0 treatment of chlorpyrifos, 44.6, 46.2, and 47.6% of the chlorpyrifos was removed within 24 h after treatment with 0.1, 0.5, and 1.0% (w/v) ferric nitrate, respectively (Fig.…”
Section: Degradation Of Chlorpyrifos By Iron Saltssupporting
confidence: 90%
“…Another pathway was reported by Ref. for the breakdown of 2,3‐dihydroxypyridine to yield maleamic acid, further oxidises to form carbondioxide, water, ammonium carbonate, and sodium chloride.…”
Section: Metabolic Pathway Involved In Degradation Of Chlorpyrifos Bymentioning
confidence: 93%
“…This showed that the immobilized carrier can protect the degrading bacteria and shield the harmful effects of the outside to a certain extent. Li Ying [30] showed that after degrading bacteria were immobilized, its tolerance to acid and alkali was significantly raised, but too acid or too alkaline also had an adverse effect on the biodegradation of chlorpyrifos (p<0.05). Compared with free bacteria, the sensitivity of immobilized bacteria to pH was decreased.…”
Section: Removal Ratio Of Ph Value On Chlorpyrifosmentioning
confidence: 99%